• Award-winning private GMAT tutoring
Register now and save up to \$200

Available with Beat the GMAT members only code

• Free Veritas GMAT Class
Experience Lesson 1 Live Free

Available with Beat the GMAT members only code

• Free Practice Test & Review
How would you score if you took the GMAT

Available with Beat the GMAT members only code

• Free Trial & Practice Exam
BEAT THE GMAT EXCLUSIVE

Available with Beat the GMAT members only code

• 1 Hour Free
BEAT THE GMAT EXCLUSIVE

Available with Beat the GMAT members only code

• Get 300+ Practice Questions

Available with Beat the GMAT members only code

• 5 Day FREE Trial
Study Smarter, Not Harder

Available with Beat the GMAT members only code

• Magoosh
Study with Magoosh GMAT prep

Available with Beat the GMAT members only code

• 5-Day Free Trial
5-day free, full-access trial TTP Quant

Available with Beat the GMAT members only code

## From Kaplan Diag. test equation

This topic has 3 member replies
Joined
10 Dec 2006
Posted:
363 messages
Followed by:
2 members
7

#### From Kaplan Diag. test equation

Wed Mar 21, 2007 6:45 am
For the equation x^2 + 2x + m = 5, where m is a constant, 3 is one solution for x. What is the other solution?

a) -5
b) -2
c) -1
d0 3
E) 5

What do you do? do you subtiutute 3 where x is? I thought it was 5...

_________________

Need free GMAT or MBA advice from an expert? Register for Beat The GMAT now and post your question in these forums!

### Top Member

Roland2rule Master | Next Rank: 500 Posts
Joined
30 Aug 2017
Posted:
405 messages
Followed by:
2 members
Fri Sep 29, 2017 2:30 pm
since 3 is one of the solutions of the quadratic equation, we will represent the whole solution with a letter say 'y'.
x=3 or x=y
and x-3=0 or x-y=0
(x-3)(x-y)=0
expanding the equation above, we have
x(x-y) - 3(x-y) = 0
x^2 - xy-3x+ 3y =0
x^2 - (y+3)x + 3y =0
Comparing this newly derived form of the equation with the original question, we observe that:
-(y+3)=2 ------------(1)
-y-3=2
-y=2+3=5
-y=5
y=-5
Hence, we obtained the other solution of the equation as required. option A is correct

Cybermusings Legendary Member
Joined
27 Mar 2007
Posted:
559 messages
Followed by:
2 members
5
Tue Mar 27, 2007 9:55 am
For the equation x^2 + 2x + m = 5, where m is a constant, 3 is one solution for x. What is the other solution?

a) -5
b) -2
c) -1
d0 3
E) 5

x^2 + 2x + m = 5

3 is one solution for x

Thus the quadratic equation has to look like

x^2 + 2x + m - 5 = 0

For 3 to be one root it has to look like this

x^2 - 3x + x + m - 5 = 0

Therefore even m - 5 = -3

Therefore m = -3 + 5 = 2

Thus x^2 - 3x + x + 2 - 5

= x ^2 - 3x + x - 3

= x(x-3) + 1(x-3)

Thus the other root of the equation is -1

I aint too good at explaining but hope this helps

### Top Member

Roland2rule Master | Next Rank: 500 Posts
Joined
30 Aug 2017
Posted:
405 messages
Followed by:
2 members
Fri Sep 29, 2017 2:30 pm
since 3 is one of the solutions of the quadratic equation, we will represent the whole solution with a letter say 'y'.
x=3 or x=y
and x-3=0 or x-y=0
(x-3)(x-y)=0
expanding the equation above, we have
x(x-y) - 3(x-y) = 0
x^2 - xy-3x+ 3y =0
x^2 - (y+3)x + 3y =0
Comparing this newly derived form of the equation with the original question, we observe that:
-(y+3)=2 ------------(1)
-y-3=2
-y=2+3=5
-y=5
y=-5
Hence, we obtained the other solution of the equation as required. option A is correct

### Best Conversation Starters

1 lheiannie07 116 topics
2 LUANDATO 68 topics
3 swerve 65 topics
4 ardz24 65 topics
5 Roland2rule 64 topics
See More Top Beat The GMAT Members...

### Most Active Experts

1 Scott@TargetTestPrep

Target Test Prep

198 posts
2 Brent@GMATPrepNow

GMAT Prep Now Teacher

181 posts
3 Jeff@TargetTestPrep

Target Test Prep

168 posts
4 Rich.C@EMPOWERgma...

EMPOWERgmat

134 posts
5 GMATGuruNY

The Princeton Review Teacher

119 posts
See More Top Beat The GMAT Experts